Application of Baylis-Hillman methodology in the synthesis of HIV-1 enzyme inhibitors - Manyeruke, Meloddy Hlatini (Rhodes University, Faculty of Science, Department of Chemistry, 2015)
The application of Baylis-Hillman methodology has afforded access to a range of Î²-hydroxypropionate ester-AZT conjugates as potential dual-action HIV-1 IN/RT inhibitors. Two families comprising a total of nine Î²-hydroxypropionate ester-AZT conjugates were synthesised. The first family was accessed using O-benzylated salicylaldehydes and methyl acrylate and the second from unprotected salicylaldehydes using tert-butyl acrylate as the activated alkene. Spectroscopic methods were employed to fully characterize the compounds. Propargylation of the respective Baylis-Hillman adducts was achieved via conjugate addition of propargylamine. The resulting products were then employed in Cu(I)-catalysed "click" reactions with azidothymidine (AZT) to yield the desired Î²-hydroxypropionate ester-AZT conjugates. Exploratory studies were also conducted to access 4-hydroxycoumarins from Baylis-Hillman derived adducts and to construct customized chiral Baylis-Hillman reaction sites. Many 4- hydroxycoumarins are known to exhibit a wide range of biological activities, and extending Baylis-Hillman methodology to access these systems is an important challenge. Two approaches were investigated. The first involved the formation of a 4-phthalimidocoumarin, aromatisation and hydrolysis of which was expected to lead to the 4-hydroxycoumarin target. The second, a variation of the first, involved the use of 4-(chrolomethyl)coumarin intermediates. Unfortunately, while various intermediates were prepared and characterised, neither approach led ultimately to the desired targets. N-substituted borneol-10-sulfonamides were constructed from camphor-10- sulfonyl chloride as chiral Baylis-Hillman reaction sites. In a preliminary study, however, none of the N-substituted borneol-10-sulfonamides exhibited Baylis-Hillman catalytic activity.
Keywords: HIV infections; Enzyme inhibitors; AZT (Drug); Bioconjugates